Characterization of Coal Porosity for Naturally Tectonically Stressed Coals in Huaibei Coal Field, China - Xiaoshi Li; Yiwen Ju; Quanlin Hou; Zhuo Li; Mingming Wei; Junjia Fan (The Scientific World Journal)
The enrichment of coalbed methane (CBM) and the outburst of gas in a coal mine are closely related to the nanopore structure of coal. The evolutionary characteristics of 12 coal nanopore structures under different natural deformational mechanisms (brittle and ductile deformation) are studied using a scanning electron microscope (SEM) and low-temperature nitrogen adsorption. The results indicate that there are mainly submicropores (2~5 nm) and supermicropores (<2 nm) in ductile deformed coal and mesopores (10~100 nm) and micropores (5~10 nm) in brittle deformed coal. The cumulative pore volume (V) and surface area (S) in brittle deformed coal are smaller than those in ductile deformed coal which indicates more adsorption space for gas. The coal with the smaller pores exhibits a large surface area, and coal with the larger pores exhibits a large volume for a given pore volume. We also found that the relationship between S and V turns from a positive correlation to a negative correlation when S>4 m2/g, with pore sizes <5 nm in ductile deformed coal. The nanopore structure (<100 nm) and its distribution could be affected by macromolecular structure in two ways. Interconversion will occur among the different size nanopores especially in ductile deformed coal.